The Effect of the Use of Initial Listening and Reading Techniques on Performance in English Language Aural-Oral Skills - Adeniyi, Moshood Raji (2015)
This study compared the effectiveness of initial listening and reading techniques on students' performance in English Language. It also examined the influence of initial reading technique on each of the listening and speaking skills with a view to improving students' aural-oral skills.